2020
DOI: 10.1101/2020.02.08.939728
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Heat Stress Responsive NAC Transcription Factor Heterodimer Plays Key Roles in Rice Grain Filling

Abstract: 22High temperature usually leads to the failure of grain filling during caryopsis 23 development, resulting in the loss of yield, however the mechanism is not yet well 24 elucidated. Here, we report that two rice caryopsis-specific NAM/ATAF/CUC domain 25 transcription factors, ONAC127 and ONAC129, respond to heat stress and are involved 26 in the caryopsis filling process. ONAC127 and ONAC129 are dominantly expressed in 27 pericarp during grain filling and can form a heterodimer. To investigate the functions 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 69 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, the Golgi marker (G‐968) and endoplasmic reticulum marker (ER‐960) were co‐transformed into rice protoplasts according to the method described in Nelson et al (2007). The fluorescent signals were detected using an SP8 confocal laser scanning microscope (TCS, Leica, German, https://www.leicabiosystems.com/) using the channel specifications described in Ren et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the Golgi marker (G‐968) and endoplasmic reticulum marker (ER‐960) were co‐transformed into rice protoplasts according to the method described in Nelson et al (2007). The fluorescent signals were detected using an SP8 confocal laser scanning microscope (TCS, Leica, German, https://www.leicabiosystems.com/) using the channel specifications described in Ren et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…NAC transcription factors are active as homodimers or heterodimers with other NACs. Rice ONAC127 is able to activate expression when assayed on its own; however, when assayed alongside its heterodimer partner ONAC129, its activity is repressed (Ren et al ., 2021). ONAC129 on its own is also an activator, so this cannot be simply explained as ONAC129 repressing ONAC127.…”
Section: Figmentioning
confidence: 99%
“…The crucial roles of some of these genes associated with Ortho-MQTLs in conferring thermotolerance can be summarized as follows: (i) mitogen-activated protein kinase cascades have been shown to be involved in signalling pathways activated by different abiotic stresses including heat stress in different plant species (Sinha et al 2011), (ii) polyamine transporter is required for the uptake of extracellular polyamines and is known to play a key role in stabilizing the mRNAs of several important heat stress-responsive genes under heat stress in Arabidopsis (Shen et al 2016), (iii) CRISPR/Cas9 based genome editing and transgenesis demonstrated a transcriptional regulatory network with two NAC genes (ONAC127 and ONAC129) coordinating multiple pathways to modulate grain development and heat stress responses at reproductive stages in rice (Ren et al 2021), (iv) a mitochondrial nucleoside diphosphate kinase (mtNDPK) is known to be involved in heat stress response in pea, possibly as a modulator of a protein (86 kilo-dalton protein) synthesized upon exposure to heat (Escobar et al 2001), (v) phospholipase D and phosphatidylinositol 4,5-bisphosphate are accumulated at the plasma membrane and nucleus, thereby regulates the ion channels and the cytoskeleton under heat stress in Arabidopsis and rice (Mishkind et al 2009), and (vi) the RNA recognition motif of Arabidopsis splicing factor affects the alternative splicing of pre-mRNAs of genes, including FLOWERING LOCUS M and a heat shock transcription factor involved in the regulation of owering and adaptation to heat stress (Lee et al 2017). Among the remaining ve ortho-MQTLs, only one ortholog matched between wheat and rice MQTLs (Table 4).…”
Section: Ortho-mqtls For Wheat and Ricementioning
confidence: 99%
“…Ortho-MQTL2B.3 contained at least two heat-responsive genes encoding for protein kinase (Sinha et al 2011) and amino acid/polyamine transporter (Shen et al 2016), respectively. Whereas, ortho-MQTL2D.1 included at least 5 heat-responsive genes encoding for the following proteins/products: NAC domain-containing protein (Ren et al 2021), nucleoside phosphatase (Escobar et al 2001), PLD-regulated protein1-like (Mishkind et al 2009), RNA recognition motif domain (Lee et al 2017), and helicase (Gong et al 2005).…”
Section: Ortho-mqtls For Wheat and Ricementioning
confidence: 99%